Pengaruh Status Sosial dan Kekuasaan dalam Komunikasi Antar Pribadi antara Gus Miftah dan Penjual Es Teh - Nadhif, Wildan; Romadhoni, Berlianti Karunia; Zuhriyah, Luluk Fikri; Purnomo, Ryan (Kamaya: Jurnal Ilmu Agama, 2024)
Social status and power have a significant influence in shaping the dynamics of interpersonal communication, especially in the context of interactions between individuals with striking differences in status. Gus Miftah, a scholar with high social status and strong religious influence, provides a unique opportunity to understand this phenomenon. This study aims to examine the influence of the difference in social status between Gus Miftah and iced tea sellers on the communication patterns that are established, as well as analyze how the power possessed by Gus Miftah affects the dynamics of these interactions in daily life. A descriptive qualitative approach is used in this study with data collection techniques in the form of observations and in-depth interviews that are analyzed thematically. This method aims to describe the communication patterns that emerge in their interactions. The results of the study show that differences in social status create complex communication dynamics, where the power and influence of Gus Miftah allow for empowering communication. Although potential obstacles such as awkwardness or inferiority from parties with lower social status can arise, Gus Miftah managed to minimize these obstacles with a communication approach full of empathy, care, and mutual respect. This not only creates a harmonious interaction, but also empowers iced tea sellers through increased motivation and confidence. In conclusion, effective communication between individuals with different social statuses can be achieved if those who have power use their influence wisely and inclusively. Gus Miftah is a clear example of how the principles of empowerment, respect, and empathy are able to overcome communication barriers, create relationships that are beneficial for both parties, and make a positive contribution to a more harmonious social life.